Proyecto de factibilidad para la producción y comercialización de cobertores para asientos de automóviles para la provincia de Loja. - ARMIJOS ACARO, FRANCISCO JAVIER (2012)
In developing the proposed research work called for the creation of a company dedicated to making car seat covers, it meets each of the structured phases where various aspects are considered such as: In the literature review was conducted a thorough analysis of all the existing information and statistical literature to discuss the background of small industry at national, provincial and local levels, which highlights that in the province of Loja industry is fleeting and that only dominates the marketing of products such as staples, clothing, footwear and more. Were used and automated office equipment and the methods were used inductive and deductive use of secondary information obtained from the Provincial Transit Loja. In the results presented the systematization of primary information obtained by applying the survey to the study population comprised of owners of vehicles cylinder capacity of up to 2000 cubic centimeters. In the discussion of the four studies presented an investment project starting with the market research which establishes an unmet demand of 1,446 sets of covers for vehicles, presents a marketing plan to engage in the implementation of this project. The technical study determined an installed capacity of 880 covers per year for a period of five years of life, the company must be located in leased premises or on the streets of Sucre and Juan Salinas and engineering shows the patent, the process production and technical requirements for the implementation of the project. The financial study consist investments totaling $ 9,500.00 financed with foreign capital and the budgets of income and expenditure, the financial statements in order to demonstrate the performance levels are structured cash flow which is the basic element make the financial evaluation of the project, with the following criteria: period of payback in 11 months and 20 days, the positive net present value of $ 35,741.73, an internal rate of return of 120.84%, the benefit cost of $ 1.17 and sensitivity analysis, which determines that the project is not sensitive to an increase in costs of 8.5% and revenues decreased by 7.3%. Finally we have the most important conclusions and recommendations to which we have come, determining that the project is feasible.